Study of copper complexes adsorbed on a silica gel surface chemically modified with 2-amino-1,3,4-thiadiazole - Dias, N. L.; Gushikem, Y.; Franco, D. W.; Schultz, M. S.; Vasconcellos, LCG (Elsevier B.V., 1998)
The isotherms of adsorption of CuX2 (X=Cl-, Br-, ClO4-) by silica gel chemically modified with 2-amino-1,3,4-thiadiazole were studied in acetone and ethanol solutions: at 298 K. The following equilibria constants (in 1 mol(-1)) were determined: (a) CuCl2: 3.5 x 10(3) (ac), 2.0 x 10(3) (eth); (b) CuBr2: 2.8 x 10(3) (ac), 2.0 x 10(3) (eth); (c) Cu(ClO4)(2): 1.8 x 10(3) (ac), 1.0 x 10(3) (eth); ac = acetone, eth = ethanol. The electron spin resonance spectra of the surface complexes indicated a tetragonal distorted structure in the case of lower degrees of metal loading on the chemically modified surface. The d-d electronic transition spectra showed that for the ClO4-, complex, the peak of absorption did not change for any degree of metal loading, and for Cl- and Br- complexes, the peak maxima shifted to a higher energy region with a lower metal loading. (C) 1998 Elsevier B.V. B.V. All rights reserved.
Keywords: copper complex with 2-amino-1,3,4-thiadiazole; electron spin resonance of copper complexes; silica gel; silica gel modified with 2-amino-1,3,4-thiadiazole; 2-amino-1,3,4-thiadiazole